DGE-seq analysis of MUR3-related Arabidopsis mutants provides insight into how dysfunctional xyloglucan affects cell elongation - Xu, Zongchang (Plant science : an international journal of experimental plant biology, 2017)
Copyright © 2017 Elsevier B.V. All rights reserved.